AKTIVITAS MODEL TEAM GAMES TOURNAMEN (TGT) BERBANTUAN MEDIA KOKAMI TERHADAP KETERAMPILAN MENULIS PARAGRAF DESKRIPSI SISWA KELAS V SEKOLAH DASAR - Hafizah; Anita Imelia Sasra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effect of the Team Games Tournament (TGT) learning model assisted by Kokami media on fifth-grade elementary students’ descriptive paragraph writing skills. A quantitative approach with a quasi-experimental pretest-posttest group design was employed. The sample consisted of 59 students, divided into an experimental group and a control group. The experimental group was taught using the TGT model supported by Kokami media, while the control group received instruction through a conventional differentiated learning method. The research instrument was a performance-based writing test assessed on content, organization, and vocabulary aspects. Data were analyzed using SPSS 23, including normality, homogeneity, and hypothesis testing via independent sample t-test. The results showed a significant increase in the average posttest scores of the experimental group compared to the control group. The significance value obtained was 0.037 (<0.05), indicating that the TGT model with Kokami media had a statistically significant positive effect. The findings suggest that combining cooperative learning strategies with interactive media can effectively enhance students’ writing abilities, foster active participation, and create a more engaging learning environment.